Translating cheese production terminology from French to Russian: Challenges and pitfalls - Vera V. Kucherova (Peoples' Friendship University of Russia (RUDN University), 2019)
This article is concerned with cheese production terminology and the appropriate ways of its translation from French to Russian. The paper will analyse French texts related to cheesemaking, describe the corresponding terms registered in French and Russian, and look into the specifics of French-to-Russian rendering of the corresponding terms. Specific attention is paid to equivalent translation, transcription, transliteration, calquing and descriptive translation as methods of translation most appropriate in cases where cheese production terminology is concerned. The following methods used in translating cheese production terminology are reviewed: replacement of the French term by the Russian term bearing the same meaning; equivalent translation; transcription; transliteration; descriptive or explanatory translation; calque translation. The author encourages translators to create a system of priorities for each individual translation case and abide by the generally accepted rules that can be applied in translating terms related to cheese production in any given set of source and target languages.